Determinants of Drug Prices in Middle Income Countries: How important are intellectual property rights? - Ingmar Schustereder; Johannes P. Jütting (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
This paper analyzes the impact of trade related intellectual property rights (TRIPS) on drug prices in seven middle income countries. Applying both an econometric as well as an explorative analysis we find three key messages: First, the introduction of TRIPS in the selected countries tends to have no major impact on the development of drug prices. Country specic factors like excessive procurement and marketing costs seem to be more important determinants for the observed high price levels. Second, the application of TRIPS safeguards which allow countries to override TRIPS requirements appears to be an important lever to contain drug prices by encouraging competition. There seems, however, scope for improvement in the efficient use of these safeguards. Third, with respect to policy implications, middle income countries should in particular address inefficiencies in local marketing and procurement costs whereas OECD countries need to improve the coherence between trade and aid policies.
Keywords: 330